The PDF4LHC report on PDFs and LHC data: results from Run I and preparation for Run II - Rojo, J.; Accardi, Alberto; Ball, Richard D.; Cooper-Sarkar, Amanda; Roeck, Albert de; Farry, Stephen; Ferrando, James; Forte, Stefano; Gao, Jun; Harland-Lang, Lucian; Huston, Joey; Glazov, Alexander; et al. (Journal of physics. G, Nuclear and particle physics, 2015)
The accurate determination of the parton distribution functions (PDFs) of the proton is an essential ingredient of the Large Hadron Collider (LHC) program. PDF uncertainties impact a wide range of processes, from Higgs boson characterization and precision Standard Model measurements to new physics searches. A major recent development in modern PDF analyses has been to exploit the wealth of new information contained in precision measurements from the LHC Run I, as well as progress in tools and methods to include these data in PDF fits. In this report we summarize the information that PDF-sensitive measurements at the LHC have provided so far, and review the prospects for further constraining PDFs with data from the recently started Run II. This document aims to provide useful input to the LHC collaborations to prioritize their PDF-sensitive measurements at Run II, as well as a comprehensive reference for the PDF-fitting collaborations.
Gesehen am 02.07.2020